2010
DOI: 10.1111/j.1539-6924.2010.01521.x
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology Risk Communication Past and Prologue

Abstract: Nanotechnologies operate at atomic, molecular, and macromolecular scales, at scales where matter behaves differently than at larger scales and quantum effects can dominate. Nanotechnologies have captured the imagination of science fiction writers as science, engineering, and industry have leapt to the challenge of harnessing them. Applications are proliferating. In contrast, despite recent progress the regulatory landscape is not yet coherent, and public awareness of nanotechnology remains low. This has led ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…Both of these inductive approaches are likely to prove most useful in characterizing people's beliefs about new technologies such as nanotechnology. ( 113 )…”
Section: Theoretical Assessment Of the Padmmentioning
confidence: 99%
“…Both of these inductive approaches are likely to prove most useful in characterizing people's beliefs about new technologies such as nanotechnology. ( 113 )…”
Section: Theoretical Assessment Of the Padmmentioning
confidence: 99%
“…Based on a risk typology that we developed several years ago, we noted that the cases presented in the articles analyzed covered a wide range, with technological or industrial risks making up a majority of the cases reviewed. More specifically, the risks involved transportation issues, food issues, energy issues, including nuclear, or cutting‐edge scientific developments such as nanotechnologies . Chemical risks and industrial risks connected with contaminated soil formed a large part of the sample .…”
Section: Resultsmentioning
confidence: 99%
“…Among the negative consequences of the events or risks in the cases we studied, health problems were the most frequently noted . The authors mainly describe the risk of contagion and death associated with the events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 It has been suggested that the erosion of trust from this issue is partly responsible for the public concerns Europeans have expressed over the safety of genetically modified foods. [6][7][8][9][10][11][12][13][14] Nanotechnologies Nanotechnologies is a collective term for a range of technologies, techniques and processes that involve the manipulation of matter at a nanoscale. The genetically modified organisms (GMOs) provide one example; others include mobile phones and phone towers, high voltage power lines, wind farms and coal seam gas extraction.…”
mentioning
confidence: 99%